Examining lean government in public services of the Badung Regency Regional Secretariat - I Gusti Agung Wiraguna; Agus Fredy Maradona (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
This research aims to determine the application of Lean government in Public Services and to obtain solutions after carrying out observations related to research problems. The research location is at the Central Regional Secretariat of Badung Regency Government. There are 3 (three) types of data collection techniques, namely observation, interviews and documentation. Data analysis in this research used several components: data reduction, data presentation, and verification. Next, data validity checking techniques are carried out. The results of the analysis conclude that the readiness for implementing public services in the Badung district government as a regional public service provider to the community is good, seen from the level of public service compliance and various innovations that the Badung district government has implemented and consistently implementing central policies, one of which is simplifying bureaucracy with the aim of To improve the quality of public services to make them more effective and efficient, one of the implementations of this central policy can be seen from the SOTK (Organizational Structure of Work Procedures) of the Regional Secretariat which has implemented this policy by equalising echelon IV officials within the Badung Regency Regional Secretariat.